THE IMPACT OF REGULATORY ACCOUNTING PROCEDURES ON THE U.S. SAVINGS AND LOAN CRISIS - Capozolli, Ernie; McGowan, Josh; Flores, Maureen (International Journal of Accounting & Finance Review, 2022)
This study explores the impact of regulatory accounting procedures (RAP) on the Savings and Loan industry during the 1980s. The Savings and Loan industry in the United States differs from commercial banks in that many of these entities are operated as cooperatives and focus on residential mortgages. Despite an increase in regulatory efforts in the 1980s, the S&L industry experienced significant failures and a lack of liquidity. Approximately one-third of the S&L entities failed during the years 1986 - 1995. This study explores multiple factors related to RAP and the S&L crisis. These factors include the voluntary adoption of RAP, organizational structure, and financial performance of the institutions. Data was collected on all S&L institutions in the state of Mississippi that were in operation as of the end of 1988. Utilizing stepwise regression this study finds that RAP was more likely to be adopted by S&L entities that operated under a mutual ownership structure when compared to S&Ls owned through stock. Results also show there was no economic benefit for those S&Ls that adopted RAP. Finally, Regulatory Net Worth was also found to be misstated in those entities that adopted RAP. The findings of this study suggest unintended consequences occurred regarding the adoption of RAP within the S&L industry. JEL Classification Codes: G21, M41, M48.